Tour de France - Hellebuyck, Adam; Deimel, Laura (21st century skills library. Global citizens: sports., 2020)
Briefly explores the history of the Tour de France bicycle race, how it became the most-watched sporting event in the world, and the rules that competitors must follow to qualify. Includes a glossary.